PENGARUH FUNGSI AUDIT INTERNAL DAN DEWAN KOMISARIS TERHADAP FEE AUDITOR PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BERSA EFEK INDONESIA - Edi Sutanto; Lisa Listiani (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
The company uses the services of a public accountant to evaluate the information that has been presented by management. The basis for determining the auditor fee can be determined from several factors, including the internal audit function and the board of commissioners. This research was conducted to determine the effect of the internal audit function and the board of commissioners on audit fees in banking companies listed on the Indonesia Stock Exchange in 2016-2018. The internal audit function which acts as an evaluator of company performance and the board of commissioners as supervisors in all company activities is expected to be able to increase the audit fees issued by the company.The data used in this study is secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange in the 2016-2018 period which are published on the website www.idx.co.id. This study used a purposive sampling method, in order to obtain a sample of 30 from 10 banking companies. Then the data analysis was carried out which included the classical assumption test, the coefficient of determination, multiple linear regression analysis, the t test, and the F test. Meanwhile, to analyze the data using SPSS version 20 software.From the data obtained, there are several banking companies listed on the Indonesia Stock Exchange in 2016-2018 whose auditor fee data experienced a loss but decreased in the following year. This means that the company has decreased so that it has an impact on auditor fees, thereby reducing auditor fees incurred by the company.Based on the research results, it is known that the internal audit function partially has no effect on audit fees, while the board of commissioners partially affects the audit fees in banking companies listed on the Indonesia Stock Exchange.